2017
DOI: 10.1007/s11356-016-8253-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring pharmaceuticals and personal care products in reservoir water used for drinking water supply

Abstract: In this work, the presence of selected emerging contaminants has been investigated in two reservoirs, La Fe (LF) and Riogrande (RG), which supply water to two drinking water treatment plants (DWTPs) of Medellin, one of the most populated cities of Colombia. An analytical method based on solid phase extraction (SPE) of the sample followed by measurement by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) was developed and validated for this purpose. Five monitoring campaigns were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 55 publications
2
20
2
3
Order By: Relevance
“…14 n. 6, e2436 -Taubaté 2019 found; the most-concentrated were atrazine (Mean: 12.1, maximum value: 19 ngL -1 , 100%), and caffeine (Mean: 3.54 μgL -1 , Maximum: 18.83 μgL -1 , 100%) (Machado et al, 2016). In a study conducted in Colombia, in the Río Grande and La Fe de Medellín reservoirs, 6 of the 9 ECs studied were found, among them ibuprofen (max 62 ngL -1 ) (Aristizabal-Ciro et al, 2017). Eleven of eighteen ECs studied were found in the Esmeraldas River, source of drinking water for the population of Esmeraldas in Ecuador; benzoylecgonine, a coca metabolite, was found with the highest concentration (Mean: 37.5 μgL -1 ) (Voloshenko-Rossin et al, 2014).…”
Section: Occurrence Of Emerging Contaminants In Surface Watersmentioning
confidence: 96%
“…14 n. 6, e2436 -Taubaté 2019 found; the most-concentrated were atrazine (Mean: 12.1, maximum value: 19 ngL -1 , 100%), and caffeine (Mean: 3.54 μgL -1 , Maximum: 18.83 μgL -1 , 100%) (Machado et al, 2016). In a study conducted in Colombia, in the Río Grande and La Fe de Medellín reservoirs, 6 of the 9 ECs studied were found, among them ibuprofen (max 62 ngL -1 ) (Aristizabal-Ciro et al, 2017). Eleven of eighteen ECs studied were found in the Esmeraldas River, source of drinking water for the population of Esmeraldas in Ecuador; benzoylecgonine, a coca metabolite, was found with the highest concentration (Mean: 37.5 μgL -1 ) (Voloshenko-Rossin et al, 2014).…”
Section: Occurrence Of Emerging Contaminants In Surface Watersmentioning
confidence: 96%
“…Equations (1)- (4) show the decomposition of water and other molecules commonly dissolved in water by sonochemical waves [9,39], being the HO•, as well as the hydroperoxyl radicals (HO 2 •), the main species that oxidizes the organic compounds present in the aqueous medium.…”
Section: Operation Fundamentalsmentioning
confidence: 99%
“…These authors investigated the presence of different inorganic anions to determine their influence on the process. The anions evaluated were Cl − , SO 4 2− and NO 3 − , and it was found that Cl − slightly restricted the degradation of the investigated drug, while the others did not have a significant impact on the degradation of the compound of interest. This slight inhibition in CBZ degradation due to the presence of Cl − can be attributed to the reaction of this ion with the HO• dispersed in the solution, resulting in the formation of ClOH• − .…”
Section: Constituents Of the Water Matrixmentioning
confidence: 99%
See 2 more Smart Citations